Photocatalytic decomposition of rhodamine B and selective oxidation of 5-hydroxymethylfurfural by β-Bi2O3/Bi12SiO20 nanocomposites produced by laser - Golubovskaya, Aleksandra G.; Kharlamova, Tamara S.; Gavrilenko, Ekaterina A.; Fakhrutdinova, Elena D.; Vodyankina, Olga V.; Kulinich, Sergei A.; Svetlichnyi, Valerii A. (Journal of composites science)
In this work, we studied the catalytic performance of a β-Bi2O3/Bi12SiO20 nanocomposite material in the reactions involving the photodecomposition of rhodamine B and selective photooxidation of 5-hydroxymethylfurfural (HMF). The semiconductor composite nanomaterial was obtained by means of the mechanical grinding of a mixture of nanopowders of β-Bi2O3 and sillenite, both individually produced via pulsed laser ablation. The crystal structure of the prepared composite particles was confirmed by means of X-ray diffraction, while the optical properties of both individual components and their composite (with different ratios of Bi2O3 and Bi12SiO20) were also studied. The photocatalytic activity of the composite particles was studied in the course of their decomposition of rhodamine B under LED excitation at wavelengths of 375, 410 and 470 nm. It was shown that the optimal β-Bi2O3/Bi12SiO20 ratio in the composite particles resulted in their photocatalytic activity exceeding those of both single-phase β-Bi2O3 and Bi12SiO20, as well as that of their mixtures (by ~2.3 times for the excitation of an LED with λ = 375 nm). The novel composite particles were also found to perform better in the selective photocatalytic oxidation of HMF: at a conversion of ~5%, the selectivity toward DFF of the nanocomposite was significantly higher (10.3%) than that of sample Bi2O3 (−4.2%). A model was proposed that explains the increase in activity of the newly prepared photocatalyst due to the formation of a type II heterojunction in its particles.